Avaliação etnofarmacológica de Jatropha isabellei, Tabernaemontana catharinensis e Viola tricolor visando desenvolvimento de formulação farmacêutica - Piana, Mariana (2012)
The plants biodiversity have a rich potential for the human health and the use of plants that containing flavonoids, alone or in combination, has grown because of their antioxidant properties.Several biological effects such as antitumor activity, antioxidant and antiinflammatory have been attributed to flavonoids, since they are able to act by modulating cell involved in inflammation. The popular knowledge, about the use of medicinal plants, is the basis for clinical, pharmacological and chemical studies, besides the development of new medicines, and the study of plants that have substances that can act on the free radicals generated in our body, is of great importance. Between the species that have antiinflammatory activity, are Jatropha isabellei and Viola tricolor, that have phytochemical studies associated to the antioxidant capacity and Tabernaemontana catharienesis which has not. This work intends to analyze between these species, the one that have potential antiinflammatory, develop a formulation and submit it to stability studies. The branches and fruits of T. Catharinensis were collected, macerated in ethanol (70%), filtered, evaporated in a rotary evaporator to remove the ethanol (aqueous extract), that has been partitioned using increasingly polar solvents: chloroform, ethyl acetate and n-butanol, an equal amount of aqueous extract was subjected to dryness resulting in the crude extract.The antioxidant activity of the branches was higher than the fruits, the content of polyphenols, condensed tannins and alkaloids had no relation with the antioxidant activity, and this result suggests that the antioxidant capacity is related not only with the quantity but also with different hydroxylation patterns of flavonoids.The study of fractions from flowers of V. tricolor conducted by Gonçalvez (2008) showed excellent antioxidant capacity, higher than those found in T. Catharinensis and J. isabellei in studies by Fröhlich (2010). Furthermore, the same author found large amounts of rutin in all fractions of V. tricolor that, for these reasons, was used in development of the gel. The flowers of V. tricolor were collected, macerated in ethanol (70%), the filtrate was evaporated in a rotary evaporator to remove the ethanol, the aqueous extract obtained was subjected to dryness obtaining the crude extract that was phytochemically analyzed and presented considerable amounts of polyphenols, flavonoids, condensed tannins, salicylic acid and small amounts of alkaloids. Methods for quantification of rutin in the gel and in the extract were validated. The developed gel was subjected to stability studies, by organoleptic analysis, pH measurements, viscosity, and quantification of rutin using the method validated. The gel showed stable as long as it remains at temperatures below 20°C.